2011
DOI: 10.1021/jp110871g
|View full text |Cite
|
Sign up to set email alerts
|

B-DNA to Zip-DNA: Simulating a DNA Transition to a Novel Structure with Enhanced Charge-Transport Characteristics

Abstract: The forced extension of a DNA segment is studied in a series of steered molecular dynamics simulations, employing a broad range of pulling forces. Throughout the entire force range, the formation of a zipper-like (zip-) DNA structure is observed. In that structure, first predicted by Lohikoski et al., the bases of the DNA strands interdigitate with each other and form a single-base aromatic stack. Similar motifs, albeit only a few base pairs in extent, have been observed in experimental crystal structures. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
28
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 78 publications
(378 reference statements)
4
28
1
Order By: Relevance
“…For instance, Balaeff et al [48] observed a B-to-zip DNA transition instead of B-to-S DNA transition using steered molecular dynamics simulations. They proposed that S-DNA could be an intermediate state during this transition.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Balaeff et al [48] observed a B-to-zip DNA transition instead of B-to-S DNA transition using steered molecular dynamics simulations. They proposed that S-DNA could be an intermediate state during this transition.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the extended DNA has been found to be consistent with a multiplicity of possible structures, from two separated strands of singlestranded DNA (ss-DNA) formed as a result of melting [14,15] to a variety of extended ds conformations (S-forms). These putative structures, including the S-ladder, a straightened DNA with preserved base pairing [16], and the S-zipper [17], are all characterized by variously coupled strands with reduced helicity. Even recently, a number of studies on the subject have appeared, either discarding [18,19] or supporting [8][9][10] the existence of the S state.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, steered MD simulations of torsionally unconstrained DNA molecules were employed [16,17,[26][27][28][29]. According to this approach, the overstretching experiments are simulated taking explicitly into account the presence of a pulling force.…”
Section: Introductionmentioning
confidence: 99%
“…10,12 Nuclear and solvent reorganization have been suggested as factors responsible for the slow rates of hole transport in DNA. 13 Among the backbone modifications that have drawn attention as alternatives to the dexoyribose of DNA in studies of charge transport are the stretched deoxyribose backbone (Zip-DNA), 14 peptide nucleic acids (PNA), 15,16 and locked nucleic acids (LNA, Chart 1b). 17,18 Molecular dynamics (MD) simulations for Zip-DNA reveal enhanced intrastrand base stacking leading to predictions of rapid charge transport, which remain to be experimentally tested.…”
mentioning
confidence: 99%